Environmental impact of sewage system in the cita del «3 may» Jipijapa City - Ecuador - Osejos Merino, Miguel Ángel (2018)
This research was carried out in the town “May 3” with a population of 7,906 inhabitants, its climate is tropical dry with a temperature of 24 ° C, its habits and customs are rooted in cultural, historical and folkloric aspects, belongs to The urban town Dr. Miguel Moran Lucio from the city of Jipijapa in the province of Manabí, where the environmental impact of the sewage system was identified from a decade ago in the citadel “May 3”, for which they were used Information collection tools such as: environmental application sheets, observation guide and survey form. With the application of these instruments the following results were obtained: the sewage system is in the final stage of service to the community, it is to collapse due to the time it has of construction and operation. The components that are affected by the sewer system are the abiotic, biotic and socioeconomic, with their respective components: air, soil, water, flora, fauna and human activities. From these components, environmental factors were determined: such as air, soil and water quality, vegetation cover and species of fauna, quality of life and well-being, health and safety. The amount of impacts found were 10, which are temporary. The significance level impacts showed a result of 19.5, which is considered moderate, the environmental component most affected and the agent or the activity that caused it: having to the conclusion that this component is the social and taken for daily living.